2005
DOI: 10.1055/s-2005-869523
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and Ticlopidine: P2Y12Adenosine Diphosphate-Receptor Antagonists for the Prevention of Atherothrombosis

Abstract: Ticlopidine and clopidogrel belong to the same chemical family of thienopyridine adenosine diphosphate (ADP)-receptor antagonists. They have shown their efficacy as platelet antiaggregant and antithrombotic agents in many animal models, both ex vivo and in vivo. Although ticlopidine was discovered more than 30 years ago, it was only recently that the mechanism of action of ADP-receptor antagonists was characterized in detail. Ticlopidine and clopidogrel both behave in vivo as specific antagonists of P2Y (12), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0
17

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(213 citation statements)
references
References 83 publications
0
196
0
17
Order By: Relevance
“…It is well known that pharmacologic inhibition of P2Y 12 with the thienopyriridine compounds ticlopidine and clopidogrel has a very good antithrombotic effect in patients at risk of cardiovascular or cerebrovascular disease [15,16]. In some clinical trials, the antithrombotic effect of these drugs proved to be superior, albeit marginally, to that of aspirin [33,34], despite the fact that thienopyridines do not adequately inhibit their pharmacological target in a relatively high percentage of treated patients [16], as opposed to aspirin, which adequately inhibits the activity of cyclooxygenase-1 (COX-1), which is its pharamacologic target [16], in the vast majority of treated patients [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that pharmacologic inhibition of P2Y 12 with the thienopyriridine compounds ticlopidine and clopidogrel has a very good antithrombotic effect in patients at risk of cardiovascular or cerebrovascular disease [15,16]. In some clinical trials, the antithrombotic effect of these drugs proved to be superior, albeit marginally, to that of aspirin [33,34], despite the fact that thienopyridines do not adequately inhibit their pharmacological target in a relatively high percentage of treated patients [16], as opposed to aspirin, which adequately inhibits the activity of cyclooxygenase-1 (COX-1), which is its pharamacologic target [16], in the vast majority of treated patients [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, P2Y 12 is the target of potent antithrombotic drugs: its irreversible inhibition by the thienopyridine drugs ticlopidine or clopidogrel effectively reduces the incidence of cardiovascular events in patients at risk [15,16]. New, promising anti-P2Y 12 drugs, such as the thienopyridine prasugrel and the direct, reversible P2Y 12 antagonists cangrelor and AZD6140, are currently under clinical development [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the fact that the potent antithrombotic thienopyridine compounds ticlopidine and clopidogrel, of which an active liver metabolite selectively and irreversibly targets the P2Y 12 receptor, were used as molecular tools to characterize platelet responses to ADP and the role of the latter in thrombosis [106]. The thienopyridine compounds are prodrugs which have to be metabolized by the liver in order to generate active metabolites.…”
Section: The Platelet P2 Receptors As Molecular Targets For Antithrommentioning
confidence: 99%
“…Large-scale clinical trials have demonstrated the beneficial effects of thienopyridines in the prevention of major cardiac events after coronary artery stent insertion and in the secondary prevention of major vascular events in patients with a history of cerebrovascular, coronary or peripheral artery disease [106,112].…”
Section: The Platelet P2 Receptors As Molecular Targets For Antithrommentioning
confidence: 99%
“…KEYWORDS: Clopidogrel resistance, clinical variability, prodrug attrition, piperidine deuteration, targeted metabolic shift, bioactivation potentiation C lopidogrel (CPG) is a thienopyridine antiplatelet prodrug that has been widely used in the treatment of cardiovascular diseases, including atherothrombosis, unstable angina, and myocardial infarction. 1 As shown in Scheme 1, CPG (M0) is activated through a two-step cytochrome P450 (CYP)-catalyzed process to form its active metabolite (M13). 2,3 Despite being one of the most prescribed cardiovascular medications of the past decade, CPG is associated with a high clinical uncertainty for its antithrombotic therapy.…”
Section: * S Supporting Informationmentioning
confidence: 99%